Antibacterial Activity of Adansonia digitata Leaf Extract against Gastrointestinal Bacterial Isolates - Muhammad, J.; Muaz, M.; Bako, G. D.; Musa, B.; Zubair, M. I. (UMYU Journal of Microbiology Research)
Study’s Excerpt: